Pancreatic hypertrophy with acinar cell nodules after longterm fundectomy in the rat. Issue 7 (July 1993) - Chu, M; Franzén, L; Sullivan, S; Wingren, S; Rehfeld, J F; Borch, K
Abstract : The effect of gastric fundectomy with hypergastrinaemia on the pancreas in rats was studied for 14 months. Rats with hypercholecystokininaemia that had had a pancreaticobiliary diversion (PBD) operation and sham operated rats served as controls. Fundectomised rats showed a significant increase in pancreatic weight and total DNA and protein content compared with sham operated rats. DNA flow cytometry showed a significantly higher ratio of tetraploid to diploid nuclei in pancreatic tissue after fundectomy than after sham operation. Mean values of all these variables were significantly lower after fundectomy than after PBD. Acidophilic atypical acinar cell foci of the pancreas were diagnosed in both fundectomised and PBD operated rats, but not in sham operated controls. The volume density and 3H-thymidine labelling index of the acidophilic atypical acinar cell foci were significantly lower after fundectomy than after PBD. Changes consistent with pancreatic adenoma were diagnosed in the PBD group only. In conclusion, fundectomy lasting about half of the life span in rats causes pancreatic hyperplasia and hypertrophy, as well as development of acidophilic atypical acinar cell foci. Although hypergastrinaemia is a prominent feature, it may not be the only factor responsible for this pancreaticotrophical effect of fundectomy.